Vinylene-linked oligothiophene–difluorobenzothiadiazole copolymer for transistor applications - Casey,A; Han,Y; Gann,E; Green,JP; McNeill,CR; Anthopoulos,TD; Heeney,M (ACS Applied Materials & Interfaces, 2016)
The synthesis of the novel donor-acceptor monomer 4,7-bis[(E)-2-(5-bromo-3-dodecylylthiophen-2-yl)ethenyl]-5,6-difluoro-2,1,3-benzothiadiazole (FBT-V2T2) is reported. Polymerization with 4,4'-ditetradecyl-5,5'-bistrimethylstannyl-2,2'-bithiophene afforded a highly crystalline polymer that aggregated strongly in solution. Polymer films were well ordered resulting in high performance field-effect transistors with low onset voltages, negligible hysteresis, high channel current on/off ratios and peak hole mobilities of up to 0.5 cm2V-1s-1. Notably the transistors exhibited close to ideal behavior with extracted mobilities almost independent of gate of voltage.